A Bulking Agent May Lead to Adrenal Insufficiency Crisis: A Case Report - Salma Ahi; Majid Esmaeilzadeh; Elham Kayvanpour; Farbod Sedaghat-Hamedani; Seyed Hossein Samadanifard (Acta Medica Iranica, 2011)
Adrenal insufficiency is a life-threatening disorder which must be treated with glucocorticoid replacement and needs permanent dose adjustment during patient's different somatic situations. Insufficient glucocorticoid doses result in adrenal crisis and must be treated with intravenous hydrocortisone. The patient was known with Adrenal insufficiency and was treated optimally with fludrocortisone and prednisolone since seven years with no history of adrenal crisis. The patient was admitted with abdominal pain, weakness, fatigue and nausea developed 3-4 days after taking psyllium, a bulking agent, prescribed by a surgeon to diagnose anal fissure. Detailed medical history, physical examinations, laboratory and imaging examinations did not approve any other cause of adrenal crisis. Psyllium may interfere with gastrointestinal absorption of prednisolone and/or fludrocortisone and trigger acute adrenal crisis in patients with adrenal insufficiency.